Minimum Capital Requirements - Ramirez, Juan (Handbook of Basel III Capital, 2017)
Any financial institution subject to Basel III regulations is required to hold certain types and amounts of capital to help it meet its obligations as they fall due. This chapter addresses the minimum capital requirements for banks. Many analyses have been performed to test the reliability of the credit‐to‐GDP gap as an indicator of excess credit growth. These analyses conclude that the credit‐to‐GDP gap indicator may have certain drawbacks and may not transmit the right signals in all circumstances concerning the build‐up and release of the buffer. The capital conservation buffer is designed to provide banks with an extra cushion of capital to draw on during times of financial and economic stress, avoiding breaching minimum capital requirements. The chapter presents a case study that covers in detail the methodology for determining G‐SIB buffers. There are two general types of regulatory capital: capital that absorbs losses on a going concern basis, and capital that absorbs losses on a gone concern basis.